Pengaruh Kompetensi Dasar Dan Motivasi Guru Terhadap Kinerja Guru (Studi Kasus Di Smk Kota Bandung) - Devi Yuniati Dradjat; Ade Mubarok (Departement of Mathematics Education, 2023)
Schools as formal educational institutions play an important role in improving the quality of education through learning to support the smooth running of development in Indonesia as a whole. Teacher competence and motivation are things that must be mastered by every teacher or teacher so that the process of delivering material from teacher to students gets results and makes graduates in their schools qualified. The test of this study was to determine how much influence the competence and motivation of teachers on teacher performance at SMK Bandung City. The results of this study are that there is a positive and significant influence on teacher competency variables and teacher motivation on teacher performance either partially or partially. Thus the competence and motivation of teachers is getting better, the better it will also affect the teacher's performance.